IMPROVING READING COMPREHENSION USING STORY IMPRESSION ON THE SECOND SEMESTER STUDENTS' AT UNIVERSITAS BHINNEKA PGRI - Ika Rakhmawati (JURNAL EDUSCIENCE (JES), 2022)
isolation. Rather, it is targeted at the students learning and analyzing the whole text, at how it is constructed to achieve its purpose (Carrell, 1996: 26)The design of this research is a classroom action research with cycle model since this research is planned to improve the students’ Reading Comprehension at the second semester of Universitas Bhinneka PGRI using Story Impression. Action research is a form of collective self-reflective enquiry undertaken by participants in social situations in order to improve the rationality and justice of their own social or educational practices, as well as their understanding of those practices and the situations in which the practices are carried out (Carr and Kemmis 1988: 5-6 in Smith, 2007).            According to the result of Test Cycle I was done in cycle I, it was found that the students who could reach the passing grade were 21 students (84%) and 4 students (16%) were failed. The criteria of success which had been determined was 80% of the students and the standard value was 80. So, the action in cycle 1 was successful.The suggestion for the students by using Story Impression, the students can know much Reading Comprehension and it makes students more active in teaching and learning process, for English lecturer should use Story Impression as alternative way in teaching Reading Comprehension and for future researcher as the reference to make a further research.